(untitled) (Open Herald: Periodical of Methodical Research, 2024)
This article delves into the concepts of similarity and identity within the domain of language studies, scrutinizing how language scholars have formulated these concepts and the methodologies they have employed in their investigation. Through an exhaustive review of existing literature, the article discerns principal themes and contentious issues about similarity and identity in language, drawing insights from empirical research. The section on research methodology delineates various approaches utilized to explore similarity and identity in language, encompassing quantitative analyses, qualitative inquiries, and experimental methodologies. Subsequently, the section on analysis and results critically evaluates findings from chosen studies, accentuating common trends and contrasting viewpoints. Lastly, the conclusion reflects on the importance of comprehending similarity and identity in language studies and proposes directions for future inquiry